ANALYSIS OF INPUT EFFICIENCY IN THE TEXTILE INDUSTRYIN DENPASAR CITY - Pedro Rasman Sembiring; I Wayan Priyana Agus Sudharma (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The manufacturing sector plays a significant role in supporting national economic growth. It is one of the main drivers of the economy due to its capacity to generate greater profits compared to other sectors. Consequently, industrialization strategies are often pursued to improve societal welfare. One such example is the textile industry in Bali Province, which holds great potential and consistently ranks among the top three industries in every regency. This study aims to analyze the effect of capital, labor, and land area on textile industry production in Denpasar City, while also examining the efficiency of these three variables using both primary and secondary data. The study employs multiple linear regression analysis with a Cobb-Douglas production function. The sample consists of 91 textile industries in Denpasar City selected using a simple random sampling technique. The results show that all independent variables simultaneously have a significant effect on textile industry production in Denpasar City. Partially, capital, labor, and land area have a positive and significant effect on production. Labor and land area were found to be inefficient, while capital was found to be not yet efficient. The textile industry in Denpasar City is currently in an increasing return to scale condition, indicating growth potential.